Pengaruh Kecerdasan Emosional, Perilaku Belajar, Motivasi, Budaya, Kesiapan, dan Kesadaran Terhadap Tingkat Pemahaman Akuntansi Pada Mahasiswa Akuntansi Kota Surakarta - Sekarayu Anlistya Nugraha, Natasha; Zulfikar, Zulfikar (Journal of Accounting and Finance Management, 2024)
This study aims to examine the relationship between emotional intelligence, learning behavior, motivation, culture, readiness, and awareness with the level of accounting comprehension among students in Surakarta. Purposive sampling was utilized in this study to sample accounting students who responded to a survey from three Suarakarta area universities.  Respondent's completed questionnaires were used to gather primary data.  Multiple linear regression analysis is the analytical technique used to quantify the effect of independent variables in accounting knowledge. The findings indicate that emotional intelligence, learning behavior, motivation, culture, readiness, and awareness significantly contribute positively to students' understanding of accounting. Regression analysis also suggests that higher values of these variables correspond to higher levels of accounting comprehension achieved.